KEMANDIRIAN BELAJAR SISWA SEKOLAH DASAR DALAM PEMBELAJARAN IPS DI MASA PANDEMIK - Ivan Stevanus; Valeria Adella; Hyzra Saradefha (STKIP Persada Khatulistiwa Sintang, 2023)
The pandemic period demands and challenges students to learn independently because independent learning determines the success of student learning. This study aims to describe the learning independence of elementary school students in a social science subject during the Covid-19 pandemic. The research subjects were 40 students in grade VI SDK Santo Kristoforus Jakarta, random sampling. This research is a qualitative case study through interviews, observation, and questionnaires as supporting instruments. Data were analyzed using qualitative analysis and inductive conclusions. The results of this study show that the independent learning of students in grade VI of Elementary Schools in Jakarta is in a Good category with an average of 72%. In order to support and realize student independence during a pandemic, a social science subject in elementary school needs to strengthen learning methods that build the capacity of students' curiosity and self-confidence to increase their self-motivation so that the aspect of student independence becomes a strong adaptive instrument in learning social science and other academic fields in pandemic situations.